Towards development of a tele‐mentoring framework for minimally invasive surgeries - Dehlela Shabir (14150565) (2023)
Background Tele-mentoring facilitates the transfer of surgical knowledge. The objective of this work is to develop a tele-mentoring framework that enables a specialist surgeon to mentor an operating surgeon by transferring information in a form of surgical instruments' motion required during a minimally invasive surgery. Method A tele-mentoring framework is developed to transfer video stream of the surgical field, poses of the scope and port placement from the operating room to a remote location. From the remote location, the motion of virtual surgical instruments augmented onto the surgical field is sent to the operating room. Results The proposed framework is suitable to be integrated with laparoscopic as well as robotic surgeries. It takes on average 1.56 s to send information from the operating room to the remote location and 0.089 s for vice versa over a local area network. Conclusions The work demonstrates a tele-mentoring framework that enables a specialist surgeon to mentor an operating surgeon during a minimally invasive surgery. Other Information Published in: The International Journal of Medical Robotics and Computer Assisted Surgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/rcs.2305